TINJAUAN IKONOGRAFI DAN IKONOLOGI POSTER IKLAN RED BULL œPOWER ON FOR STRENGTH - Desiana Muryasari; Rohiman Rohiman; Iqbal Mahendra (Fakultas Bahasa dan Seni Universitas Negeri Medan, 2024)
Red Bull is an energy drink brand owned by Red Bull GmbH from Austria. With a share of Red Bull is an energy drink brand owned by Austrian company Red Bull. With a market share of 38%, Red Bull became the world's most popular energy drink brand in 2019. Rather than relying on traditional marketing methods, Red Bull gained attention and built a œbrand myth through several extreme sports series. Red Bull has repeatedly used nonverbal forms of signs and signals (icons) when designing advertising posters for its products. What is interesting to study is that the symbols used in Red Bull product advertisements have an important and lasting role. The purpose of this study is to identify the signs and markings on Red Bull's œPower on for Strength advertising posters. The qualitative research method uses a historical approach. This research review is historical and based on Erwin Panofsky's theory of iconography and iconology. Translated with DeepL.com (free version). The iconography review emphasizes the themes and concepts in the Product advertising posters. The first conclusion regarding the visual design of the Red Bull œPower On For strength advertising poster has factual and representational meanings. The main object is factual in the object of can packaging and the Power icon which is explicitly an expression of Red Bull can packaging is strength. The second conclusion is the theme of the advertisement about the representation of recognizable objects. The representation of familiar objects is often used to express the objective relationship between the sign of an object in the icon and the real object. The third conclusion is the meaning of the Red Bull advertising poster œPower On For Strength Red Bull product identification process through the shape and icon of power on the object of can packaging. The can packaging symbolizes the product name Red Bull, and the Power icon as a sign of power. Using the power icon means that drinking Red Bull increases energy in the body, in other words making you feel like you just woke up.Keywords: Advertising, Poster, Iconography, Iconology, RedBullAbstrakRed Bull merupakan sebuah merek minuman energi milik Red Bull GmbH asal Austria. Dengan pangsa Red Bull adalah merek minuman energi yang dimiliki oleh perusahaan Austria Red Bull. Dengan pangsa pasar sebesar 38%, Red Bull menjadi merek minuman energi terpopuler di dunia pada tahun 2019. Daripada mengandalkan metode pemasaran tradisional, Red Bull mendapatkan perhatian dan membangun